Catastrophic Politics : How Extraordinary Events Redefine Perceptions of Government - Atkeson, Lonna Rae; Maestas, Cherie D. (Cambridge : Cambridge University Press, 2012)
Shocking moments in society create an extraordinary political environment that permits political and opinion changes that are unlikely during times of normal politics. Strong emotions felt by the public during catastrophes - even if experienced only vicariously through media coverage - are a powerful motivator of public opinion and activism. This is particularly true when emotional reactions coincide with attributing blame to governmental agencies or officials. By examining public opinion during one extraordinary event, the aftermath of Hurricane Katrina, Lonna Rae Atkeson and Cherie D. Maestas show how media information interacts with emotion in shaping a wide range of political opinions about government and political leaders. Catastrophic events bring citizens together, provide common experiences and information, and create opinions that transcend traditional political boundaries. These moments encourage citizens to re-examine their understanding of government, its leaders and its role in a society from a less partisan perspective.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).